Pola Komunikasi Gerakan Sosial Komunitas Sekitar Tambang Migas Tiaka: Refleksi Identitas Etnik Lokal - Ilyas Lampe (Asosiasi Pendidikan Tinggi Ilmu Komunikasi (ASPIKOM), 2018)
This study aims to reveal the communication patterns of social community movements that seek to gain economic access to oil and gas mining operation in Tiaka. The social movement of the local community stems from the ban of fishers, originated from the coastal villages in the oil and gas circle of Tiaka, to enter Sapa Mataha, the coral reefs that become fishing ground that promises life for fishermen families around mainly Bajo ethnic for decades. The research method used is interpretative perspective with case study approach. Data were collected through in-depth interviews, observations and document reviews. The results show that community leaders (actors) build solidity and collective narratives that unite different ethnic groups around the affected areas of Tiaka oil and gas mining operation. The main messages that arise in the communication activities from the awareness, socialization, and advocacy stages are the idioms of sapa mataha, tanah ulayat, indigenous peoples and CSR. The discourse is constructed from the ethnic identity of Bajo and Taa’. The actors’ awareness and advocacy efforts utilize a variety of communication media including face to face meetings, community meetings, focus group discussions (FGD), pamphlet, blogs on the internet and Facebook. This communication process then spawned community awareness, thus forming ethnic-based forums and regional associations for mobilizing, rallies and up to sabotage efforts.